VD_FINDINFO MP / 2019 / 3 vom 9. November 2018 - VD Tribunal cantonal (2018)
DROIT DE LA FONCTION PUBLIQUE, MESURE PROVISIONNELLE, TRANSFERTEN GÉNÉRAL, PROTECTION DE LA PERSONNALITÉ | 328 CO, 16 LPers-VD, 21 LPers-VD, 22 LPers-VD, 37 RLPers-VD, 261 CPC (CH), 3a LHC